HUKUMAN CAMBUK BAGI PELAKU JARIMAH ZINA DALAM HUKUM PIDANA ISLAM ( Studi Putusan MAHKAMAH Syar’iyah Lhokseumawe Nomor 4/JN/2018/MS.Lsm ) - Zama, Aditya (Fakultas Agama Islam, 2020)
Islamic criminal law considers that every perpetrator of adultery or a person who engages in sexual relations outside of marriage is punishable by punishment, whether the perpetrator is married or not, whether they are consensual or not, because Jarimah (criminal act) for adultery in Islamic law is categorized as Jarimah hudud. The formulation of the problem in this paper is as follows, how are the rules of caning for adultery perpetrators in Islamic criminal law, how is the application of sanctions / canings against the perpetrators of zina zina in Islamic criminal law, how are judges' legal considerations in the application of flogging law against adultery perpetrators based on the decision of the Lhokseumawe Syar'iyah Court. The type of research in this research is normative legal research with a normative juridical approach. Normative legal research is also called doctrinal legal research, where law is conceptualized as what is written in laws and regulations (law in books) and research on legal systematics can be carried out if there are certain statutory regulations or written law. The data collection technique in this research is library research, which is